2020
DOI: 10.1186/s13567-020-00823-8
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate-mediated autophagy inhibition limits cytosolic Salmonella Infantis replication in the colon of pigs treated with a mixture of Lactobacillus and Bacillus

Abstract: Probiotics as an effective and safe strategy for controlling Salmonella infection are much sought after, while autophagy is a central issue in eliminating intracellular pathogens of intestinal epithelial cells. In this study, an animal model of colitis has been developed by infecting weaned pigs orally with a strain of Salmonella Infantis in order to illuminate the potential efficacy of a mixture of Lactobacillus and Bacillus (CBB-MIX) in the resistance to Salmonella infection by regulating butyrate-mediated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…[ 34 ] Lipidation of light chain 3 (LC3) occurs during canonical autophagy which converts from LC3‐I to LC3‐II, Salmonella infection in the colon activates the conversion in intestinal epithelial cells. [ 35 ] This study showed that Salmonella infection inhibited the phosphorylation of proteins in the AKT/mTOR/p70S6K pathway and caused autophagy in colon which confirmed by the increase ratio of LC3‐II to LC3‐I ( Figure 5 A,B). Genistein increased the phosphorylation level of AKT/mTOR/p70S6K protein to alleviate the inflammation caused by Salmonella infection.…”
Section: Resultsmentioning
confidence: 77%
“…[ 34 ] Lipidation of light chain 3 (LC3) occurs during canonical autophagy which converts from LC3‐I to LC3‐II, Salmonella infection in the colon activates the conversion in intestinal epithelial cells. [ 35 ] This study showed that Salmonella infection inhibited the phosphorylation of proteins in the AKT/mTOR/p70S6K pathway and caused autophagy in colon which confirmed by the increase ratio of LC3‐II to LC3‐I ( Figure 5 A,B). Genistein increased the phosphorylation level of AKT/mTOR/p70S6K protein to alleviate the inflammation caused by Salmonella infection.…”
Section: Resultsmentioning
confidence: 77%
“…These phyla degrade the nutrients present in the distal gut to a variety of metabolites producing short-chain fatty acids (SCFAs), with acetate, propionate and butyrate being the most abundant [ 36 ]. Interestingly, several studies have demonstrated the effects of propionate and butyrate production in the prevention of Salmonella colonization [ 37 , 38 , 39 ]. In fact, our results confirm higher abundance of Clostridium , Turicibacter , Bacteroidaceae_uc, and Lactobacillus in Salmonella -negative animals, all genera associated with the production of these two SCFAs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAC-T cells were cultivated on cell climbing sheets for staining and treated as described above ( 47 ). For labeling the mitochondria, Mito-Tracker Red CMXRos (CMXRos, C1035, Beyotime Biotechnology, Shanghai, China) was added to living MAC-T cells at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…At 8 h after E. coli challenged, MAC-T cells were harvested and fixed in 3% glutaraldehyde (pH = 7.4) for 48 h. Samples were treated following the standard TEM procedure (15,46). Immunofluorescence MAC-T cells were cultivated on cell climbing sheets for staining and treated as described above (47). For labeling the mitochondria, Mito-Tracker Red CMXRos (CMXRos, C1035, Beyotime Biotechnology, Shanghai, China) was added to living MAC-T cells at 37°C for 30 min.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%